2009
DOI: 10.1111/j.1600-0838.2008.00844.x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of enjoyment when promoting physical exercise

Abstract: The purpose of this study was to investigate the importance of enjoyment of exercise in a health care-based intervention aimed at promoting physical exercise in primary health care patients. In a controlled study design, the intervention group was offered a wide range of group exercises over 3 months, followed by support in designing their own exercise program. The control group received usual care. Enjoyment of exercise and exercise level were measured. Associations between enjoyment and exercise level were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
1
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(123 citation statements)
references
References 27 publications
(27 reference statements)
7
105
1
10
Order By: Relevance
“…As such, the results simultaneously showing greater enjoyment at T3 for both exergame and control groups, and yet reduced enjoyment from T1 to T2 for the control group suggests that this control measure was indeed effective. Research has reported the benefits of enjoyment on sport participation in that those with higher enjoyment tend to be more committed to the sport (Hagberg et al, 2009). This evidence is also further supported when considering the attrition of the current project was a mere 9% whereas the typical attrition rates for exercise interventions with behavioral components fall in between 18%…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, the results simultaneously showing greater enjoyment at T3 for both exergame and control groups, and yet reduced enjoyment from T1 to T2 for the control group suggests that this control measure was indeed effective. Research has reported the benefits of enjoyment on sport participation in that those with higher enjoyment tend to be more committed to the sport (Hagberg et al, 2009). This evidence is also further supported when considering the attrition of the current project was a mere 9% whereas the typical attrition rates for exercise interventions with behavioral components fall in between 18%…”
Section: Discussionmentioning
confidence: 99%
“…Past research has found positive associations between exercise intensity and enjoyment, as well as for adherence rates and enjoyment (Hagberg, Lindahl, Nyberg, & Hellénius, 2009). Studies such as this suggested that enjoyment was an important mediator of exercise.…”
Section: Exergame Research and Specific Populationsmentioning
confidence: 98%
“…Yu et al (2015) showed its utility for Alzheimer patients and Tiozzo et al (2015) for stroke patients. However, repetitive exercise with aerobic benefits can be boring; indeed, Hagberg et al (2009) found in a study that enjoyment is important in increasing physical exercise.…”
Section: Exercisementioning
confidence: 99%
“…In this context, Teel et al 8 note that music plays a significant role in the success of exercise sessions; therefore, it is relevant that practitioners choose background music that contribute to the pleasure of the exercise environment and boosts motivation. Musical accompaniment during physical activity can reinforce a sense of dissociation or disconnect 9 or a "state of flow" 10,11 , in which the practitioner would be intrinsically motivated for and fully involved and absorbed in the activity. Eccording to Csikszentmihalyi 10 , the experience of "flow" would be accompanied by a narrowing of perception, an increase in self-awareness, and a sense of oneness with the activity and the environment, thus heightening positive and pleasurable feelings.…”
Section: Introductionmentioning
confidence: 99%